Syndromic surveillance in COVID-19 pandemic control: experience and comparison among countries - Xiaowen WANG; Xiaoyi QIU; Lizhong DUAN (Editorial Office of Chinese Journal of Public Health, 2023)
Syndromic surveillance is a critical component of intelligent warning and multi-point event-triggered mechanism for surveillance on public health emergency. In this paper using literature analysis, we discussed the characteristics of syndromic surveillance implemented during coronavirus disease 2019 (COVID-19) pandemic and summarized performance experiences of those syndromic surveillance programs in typical countries or regions for providing a reference to construct effective syndromic surveillance framework in China.